The use of a higher-dimensional analysis to investigate training load `dose-response` relationships in professional youth rugby league players - Weaving, D.; Jones, B.; Whitehead, S.; Ireton, M.; Bargh, M. (Journal of Australian Strength and Conditioning, 2017)
Understanding the required training load to elicit improvements in intermittent running performance is a crucial process for strength and conditioning coaches. The aim was to investigate whether internal and external training load (TL) variables are related in a `dose-response` manner with changes in 30-15 intermittent fitness test (30-15IFT) performance following a period of training.